Work Atmosphere and Perception on Job As Determinant Factor of Employee’s Intention To Stay in Wahyu Tutuko Police Hospital Bojonegoro - Nyoman Anita Damayanti (Universitas Airlangga, 2013)
Introduction: Many studies suggested that employee intention to stay were determined by job satisfaction, particularly correlated with salary or other economic aspects. However, the initial survey showed that 55 % of employees in Wahyu Tutuko Police Hospital Bojonegoro had a low job satisfaction although still remained in. It seems that there are other factors in determining the employee’s intention to stay; the most possible one is work atmosphere. This study aimed to analyze the relationship between work atmosphere and the employee’s intention to stay.Method: This is an analytical study in observational design study with cross sectional approach. There were 95 employees participated as research sample in accordance with the inclusion and exclusion criteria. Data collected with the questionnaire guides. Work atmosphere variable is associated by the feelings of employees on the job and the work environment includes employment status, pride in the organization, a guarantee of future career and comfort working environment.Result: In order sequences, the main determinant of work atmosphere were associated with the employee’s intention to stay, then the proudness in hospital, comfortable working environment, employment status, confidence of future careers guarantee, a sense of dedication and responsibility. Discussion: This study concluded that beside employee status, the main determinant in predicting intention to stay are work atmosphere, pride on organization and the faith of future in the organization.